2017
DOI: 10.4111/icu.2017.58.3.171
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary oncologic outcome and postoperative complications in patients undergoing robot-assisted radical cystectomy: Initial experience

Abstract: PurposeRobot-assisted radical cystectomy (RARC) was originally intended to replace open radical cystectomy (ORC) as a minimally invasive surgery for patients with invasive bladder cancer. The purpose of this study was to evaluate the advantages of robotic surgery, comparing perioperative and oncologic outcomes between RARC and ORC.Materials and MethodsBetween June 2012 and August 2016, 49 bladder cancer patients were given a radical cystectomy, 21 robotically and 28 by open procedure. We compared the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The general characteristics of the eligible studies are summarized in Table . The present systematic review includes six RCTs comprising 581 patients, and 31 NRCTs comprising 48 392 patients published between 2010 and 2018. Of these, 20 studies enrolled patients from North America, nine from Europe and eight from Asia.…”
Section: Resultsmentioning
confidence: 99%
“…The general characteristics of the eligible studies are summarized in Table . The present systematic review includes six RCTs comprising 581 patients, and 31 NRCTs comprising 48 392 patients published between 2010 and 2018. Of these, 20 studies enrolled patients from North America, nine from Europe and eight from Asia.…”
Section: Resultsmentioning
confidence: 99%
“…In our 10-year cohort, complications were reported in 89 patients with an overall complication rate of 56.3%. Although only 9 patients of this cohort underwent RARC, previous studies have shown that complication rates of ORC are comparable to those of RARC [4,18,20,21]. RARC has been proven equivalent to the open approach in terms of oncological and functional outcomes, with less blood loss, fewer transfusion, shorter hospital stays and quicker recovery [21].…”
Section: Discussionmentioning
confidence: 78%
“…Most of the available studies have analysed data from large population datasets or referral centers with high patient-and surgeonvolumes [5,[12][13][14][15][16], whereas a small number of reports deals with perioperative, oncological outcomes and complications in a low volume centers, where many RC are performed. Most of monocentric studies have focused their attention on specific surgical techniques or compared operative outcomes of different surgical approaches [18,19]. To our knowledge the current series represents the first report of outcomes of RC performed in a low-volume center by experienced surgeons that provides a comprehensive overview of results for different surgical techniques, reflecting the reality of most institutions.…”
Section: Discussionmentioning
confidence: 99%
“…That nding might re ect the universal health reimbursement provided through employee-and community-based social health insurance in Japan and the existing local traditions [24]. In previous Japanese studies, Muto et [25,26]. Third, ERAS implementation at our institution involved only a few potential ERAS elements.…”
Section: Discussionmentioning
confidence: 94%